In Vitro Activity of Piperacillin Compared with That of Carbenicillin, Ticarcillin, Ampicillin, Cephalothin, and Cefamandole Against Pseudomonas aeruginosa and Enterobacteriaceae - Shah, Pramod P. (1979)
Piperacillin (T-1220), a semisynthetic derivative of aminobenzylpenicillin, was more active than either carbenicillin or ticarcillin against Pseudomonas aeruginosa; over 60% of isolates were inhibited at a concentration of 6.3 μg/ml. Piperacillin was bactericidal for 84% of Pseudomonas strains at 100 μg/ml, carbenicillin killed 60%, and ticarcillin killed 68% at that concentration. Piperacillin was also more active than the other penicillins against isolates of Escherichia coli, Enterobacter, and Proteus mirabilis. The combination of piperacillin and tobramycin, demonstrating synergistic inhibition of 87% of strains of P. aeruginosa, was the most active of the penicillin-aminoglycoside combinations tested for synergism.